45 Implementation of a consensus-based nutritional pathway for pre-surgical infants with congenital heart disease improves pre-operative growth. (23rd February 2023) - Kidd, Catherine; Rothman, Brittany; Dedieu, Nathalie; O'Sullivan, Aileen; Green, Amber; O'Connor, Graeme
Abstract : Background: Better pre-operative growth is correlated to improved post-operative outcomes for infants with congenital heart disease (CHD). A consensus-based nutritional guidelines for these patients was published in 2018. This study aimed to assess growth and clinical outcomes pre- and post-implementation of this guideline. Methods: A single-centre retrospective review was performed in a tertiary cardiac centre between June 2019 (pre-implementation) and August 2021 (post-implementation). The time-lapse allowed service establishment. Infants who were admitted to CICU post-operatively with a primary diagnosis of a 'high nutritional risk' lesion were included. Primary outcomes were weight-for-age-z-scores (WAZ) at three time points: birth, referral to dietetic service and surgery; secondary outcomes were CICU length of stay (LOS), hospital-LOS, days ventilated and age at surgery. Data was extracted from the patient record by a dietitian and analysed using paired and independent t-tests through SPSS. Results: 20 infants in the pre-service group (receiving no or community dietetic input) and 19 infants in the post-service group (specialist tertiary cardiac dietetic input following the guideline) were recruited. There was no significant difference between the pre- and post-service mean birth WAZ -1.13(±1.06 SD) and -0.80(±1.21) respectively; p =0.263 (95% CI: -1.14, 0.32). The mean surgery WAZ was significantly lower in the pre-service group -2.13 (±1.72), compared to post service group -0.99 (±1.18); p =0.018 (-2.14, 0.21). In the post-service group, mean birth WAZ 0.81 (±1.21) was significantly higher than WAZ at referral -1.49 (±1.16) p=0.001 (95% CI:0.31, -0.06). The mean referral WAZ -1.49 (±1.16) was significantly lower than surgery WAZ -0.99 (±1.21) p=0.008 (95% CI:-0.86, -0.15). Age at surgery, days ventilated post op, CICU-LOS, hospital-LOS and age at surgery decreased in the post-service group; although not statistically significant this may be attributable to a small sample size and could be clinically significant. Conclusion: Specialist dietetic input following this consensus-based guideline improves growth at surgery.